2011
DOI: 10.1111/j.1944-8287.2011.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of New Businesses to Regional Employment-An Empirical Analysis

Abstract: Key words: entrepreneurship new business formation regional development employment ECONOMIC GEOGRAPHY 87(2):153-180.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Given the macrofindings by Holmlund and Storrie [73], it is reasonable to expect that many of the created jobs are based on fixed-term contracts but where these types of jobs are created and for which groups remains to be seen. Moreover, by studying the geography of entrepreneurship and spin-offs [69] it would be possible to discern in more detail how the intraurban economy evolves if addressing questions like where new firms of various forms (start-ups of spin-offs) in different sectors enter and how the location of entrepreneurship influences survival power and employment growth [74].…”
Section: Discussionmentioning
confidence: 99%
“…Given the macrofindings by Holmlund and Storrie [73], it is reasonable to expect that many of the created jobs are based on fixed-term contracts but where these types of jobs are created and for which groups remains to be seen. Moreover, by studying the geography of entrepreneurship and spin-offs [69] it would be possible to discern in more detail how the intraurban economy evolves if addressing questions like where new firms of various forms (start-ups of spin-offs) in different sectors enter and how the location of entrepreneurship influences survival power and employment growth [74].…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies have identified the factors, characteristics, and conditions perceived as fundamental to the development of entrepreneurial activity in a region (e.g. Bull & Winter 1991;Fritsch & Schindele, 2011). These studies identify six important domains of the entrepreneurial ecosystem: social and demographic, economic, technological, financial, infrastructural, and policy.…”
Section: Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…While economic factors like GDP growth, unemployment, and human capital explain a great deal of the variation in economic activity between regions, social and cultural factors remain important source of differentiation (Davidsson and Wiklund, 1997). Given the role of entrepreneurship in generating resilient regional economies, research on the local cultural factors that encourage or discourage the creation of innovative startups has become a point of paramount importance (Fritsch and Schindele, 2011). The relational connections between local cultures and entrepreneurship are complex and difficult to untangle, but difficult to ignore.…”
Section: 2: Entrepreneurial Geographies and Environmentsmentioning
confidence: 99%